Kant and the demandingness of the virtue of beneficence. (25th April 2019) - Formosa, Paul; Sticker, Martin
Abstract: We discuss Kant's conception of beneficence against the background of the overdemandingness debate. We argue that Kant's conception of beneficence constitutes a sweet spot between overdemandingness and undemandingness. To this end, we defend four key claims that together constitute a novel interpretation of Kant's account of beneficence: (1) For the same reason that we are obligated to be beneficent to others, we are permitted to be beneficent to ourselves; (2) we can prioritise our own ends; (3) it is more virtuous to do more rather than less when it comes to helping others; and (4) indifference to others is vicious. Finally, we explain how this represents a system of duties that gives our personal ends a moral standing without unacceptably moralising them.